Study the Effect of DBD Plasma on the Mechanical Properties of Polymer PMMA/HA - Jasim; Salma S. Abdullah; Saif Khalel Jasim; Ayat Hussein Ghazi (Indonesian Journal of Material Research, 2025)
Recent studies on plasma generated at atmospheric pressure have become increasingly significant, with researchers intensifying their focus on its practical applications, particularly in industrial and medical fields. DBD plasma has been utilized in this study to examine the mechanical properties of compound materials (PMM/HA) synthesized in the laboratory. The compressive strength results indicate a gradual increase in stress and Young’s modulus with increasing time before and after the plasma treatment, also hardness levels were found to have improved, before and after the plasma treatment (63.3, 71.3, 73, and 74.3) respectively. Either the bending test result increased post-impact, with a notable enhancement corresponding to extended time periods. DBD plasma had a much bigger effect on bending strength. The polymer and hydroxyapatite showed a rise from 63.31 MPa before impact to 74.4 MPa after 90 seconds. This shows that the samples’ mechanical properties get better with longer plasma exposure. Method A base material made of PMMA polymer was added to with a nanomaterial made of hydroxyapatite (HA) to make a bioceramics compound. We conducted hardness, bending, and tensile tests to investigate the influence of DBDon the mechanical properties of nanocomposite materials. Nanosized materials (PMMA/HA) showed a big improvement in their properties after plasma treatment for three different lengths of time (30, 60, and 90 seconds). This shows that the samples’ mechanical properties get better with longer plasma exposure.